Reviewing on influence of waste materials on structural concrete under impact loading. (28th December 2021) - Sharma, Rachit; Senthil, K.
The response of concrete with waste materials under impact loading are explored through detailed literature review. The effect of percentage of waste incorporation, size of waste aggregate, volume fraction of fibre and size of fibre is reviewed in terms of energy absorption, failure mode, dynamic compression and tension under three commonly used impact tests. Based on the survey, the benefits and significance of waste materials on incorporation of concrete is presented. The better performance was observed for the use of hybrid fibres over individual fibres even at high volume additions. It was suggested for potential usage of eco-friendly concrete using recycled coarse aggregate and rubber particles for roadways, walkways, highway barriers and protective structures against impact loading. The rubber particles up to 15% for coarse aggregate replacement in concrete have been recommended under low velocity impact loading. The coir fibres have absorbed highest impact energy with maximum value for 2% fibre volume and 40 mm fibre length and it has highest residual impact strength ratio among other natural fibres. The suggested future areas of research of waste materials on concrete under dynamic loading are rice husk ash, sugarcane bagasse ash, waste foundry sand, sugarcane and nylon fibres.